Early Intervention in Psychosis in the United States: From Science to Policy Reform. (March 2017) - Breitborde, Nicholas J. K.; Moe, Aubrey M.
Available data have demonstrated the clinical benefits and cost-effectiveness of multi-component treatment packages for individuals early in the course of psychotic-spectrum disorders. In response, an unprecedented effort aims to disseminate such multi-component treatment programs—referred to as Coordinated Specialty Care (CSC)—throughout the United States. We review the evidence in support of CSC care for first-episode psychosis and highlight specific policy reforms that may facilitate the successful dissemination and eventual improvement of CSC programs for first-episode psychosis. Among proposed reforms are novel financing strategies for CSC services and incentivizing of continued collaboration between academic and community agencies to facilitate sustained dissemination and refinement of CSC.